Willingness of university nursing students to volunteer during the COVID-19 pandemic in Brunei Darussalam - Hj Abdul Aziz, Amal Atiqah Hamizah; H. Abdul-Mumin, Khadizah; Abdul Rahman, Hanif (Belitung Raya Foundation, Indonesia, 2021)
Background: Volunteering among nursing students has become a valuable resource during an outbreak to help alleviate the strain in nursing staff shortages. However, evidence of willingness to volunteer is scarce, particularly in Asian countries.Objective: To study Bruneian university nursing students’ willingness to volunteer during a pandemic in Brunei. Methods: An online cross-sectional study was conducted at Universiti Brunei Darussalam from January to February 2021. A self-administered questionnaire was used to measure willingness factors, including motivational factors, barriers, enablers, and level of agreement to volunteer during the COVID-19 pandemic. Sub-group inferential analysis was applied. Results: 72 participants were included in this study. 75.0% of whom were willing to volunteer during the COVID-19 pandemic. Factors that influenced the willingness of nursing students to volunteer were marital status (p <0.001), year of study (p <0.001), altruism (p <0.001), personal safety (p <0.001), and knowledge level (p <0.001). Conclusion: Nursing students are an invaluable resource, and they are highly willing to be part of disaster management. Training and planning should prepare the nursing students for disaster or pandemic readiness and integrated them into the undergraduate nursing curriculum. Align with this, safety aspects of nursing students during volunteering should also be considered, including the provision of childcare assistance, sufficient personal protective equipment, vaccination, and prophylaxis to the volunteers.